Hemoglobin A1c and fructosamine correlate in a patient with sickle cell disease and diabetes on chronic transfusion therapy. Issue 9 (3rd July 2020) - McLean, Ashley; Wright, Frances; deJong, Neal; Skinner, Sarah; Loughlin, Ceila E.; Levenson, Amy; Carden, Marcus A.
Abstract: In patients with sickle cell disease (SCD) and diabetes mellitus (DM), hemoglobin A1c (HbA1c ) is unreliable and the American Diabetes Association recommends monitoring long‐term glycemia by measuring serum glucose, but use of serum fructosamine (SF), a measurement independent of red cell lifespan, has been reported. SF as a screen for DM in SCD, however, is not standardized and its relationship to serum glucose has not been validated. Further, screening for DM was not adequately addressed in the 2014 National Heart, Lung, and Blood Institute (NHLBI) guidelines for SCD management. Blood transfusions, an important treatment for some patients with SCD, can also impact HbA1c . We present a case of a patient with SCD and cystic fibrosis‐related diabetes on monthly chronic transfusions therapy (CTT) who had well‐correlated "steady state" HbA1c and SF levels over time, suggesting for the first time these markers may actually be useful when following long‐term glycemic control in patients with SCD on CTT programs.